Advances in nanostructures fabricated via spray pyrolysis and their applications in energy storage and conversion. (17th May 2019) - Leng, Jin; Wang, Zhixing; Wang, Jiexi; Wu, Hong-Hui; Yan, Guochun; Li, Xinhai; Guo, Huajun; Liu, Yong; Zhang, Qiaobao; Guo, Zaiping
Abstract : This review provides insight into various nanostructures designed by spray pyrolysis and their applications in energy storage and conversion. Abstract : Functional nanostructured materials have attracted great attention over the past several decades owing to their unique physical and chemical properties, while their applications have been proven to be advantageous not only in fundamental scientific areas, but also in many technological fields. Spray pyrolysis (SP), which is particularly facile, effective, highly scalable and suitable for on-line continuous production, offers significant potential for the rational design and synthesis of various functional nanostructured materials with tailorable composition and morphology. In this review, we summarize the recent progress in various functional nanostructured materials synthesized by SP and their potential applications in energy storage and conversion. After a brief introduction to the equipment, components, and working principles of the SP technique, we thoroughly describe the guidelines and strategies for designing particles with controlled morphology, composition, and interior architecture, including hollow structures, dense spheres, yolk–shell structures, core–shell structures, nanoplates, nanorods, nanowires, thin films, and various nanocomposites. Thereafter, we demonstrate their suitability for a wide range of energy storage and conversion applications, including electrode materials for rechargeable batteries, supercapacitors, highly active catalysts for hydrogen production, carbon dioxide reduction and fuel cells, and photoelectric materials for solar cells. Finally, the potential advantages and challenges of SP for the preparation of nanostructured materials are particularly emphasized and discussed, and several perspectives on future research and development directions of SP are highlighted. We expect that this continuous, one-pot, and controllable synthetic technology can serve as a reference for preparing various advanced functional materials for broader applications.